Newly discovered vital population of the European pond turtle Emys orbicularis in Prilipe oxbow lakes (SE Slovenia) - Marijan Govedič; Gregor Lipovšek; Nino Kirbiš; Tea Bizjak Govedič; Melita Vamberger (Natura Sloveniae)
In this study we examined the population of the European pond turtle (Emys orbicularis) in the Prilipe oxbow lakes along the Sava River. The species’ sex and age structure were estimated as well its population size. In the area of approximately 5.9 ha of water surface, 3 individuals were found in 2008 and 70 in 2019, when a more detailed survey was conducted. The population size was estimated at 125 individuals. According to the age structure and confirmed reproduction, the population is recognized as viable. The main threats to the survival of European pond turtles in this area are potential direct interventions into habitat as well as indirect changes such as alterations in flood regime or in groundwater level. Additionally it is threatened by the invasive red-eared slider (Trachemys scripta elegans), the reproduction of which was also confirmed during our survey. Although the studied area meets all conditions for the establishment of the Natura 2000 site, it was not included in this network in 2003 due to lack of knowledge as far as this species was concerned.